Developing personas and proto personas to enhance the art museum visitor experience - Luz, F. G. da.; Ferreira, P. A.; Neves, J. S. (Keep it Simple, Make it Fast!: An approach to underground music scenes, 2021)
This paper aims to study and think about the use of personas and proto personas on the art museum visitors’ experience. Its object of study is the educational services of art museums focusing on children and young people up to the age of 18. This is a hybrid - conceptual and empirical – and exploratory study. Conducted through a qualitative methodology, constructivist paradigm and design approach. It relies on critical and creative thinking, as well on data collection. Using a total of 36 interviews to teachers/educators and legal tutors, divided into two distinct phases, and three pre-test interviews. It expands the investigation of application of the construction of personas and proto personas in the management of educational services in art museums. The value of this study lies in exploration of the construction of personas and in a learning context Do - Feel - Learn instead of the traditional “Learn - Feel - Do”.